Pragmatic markers in World Englishes: 'Kind of' and 'Sort of' as a case in point (2024)
This book contributes to the field of pragmatic variation in World Englishes by analysing the pragmatic markers ‘kind of’ and ‘sort of’. After a general review of their history and current use, the book offers a contrastive study of their frequency, semantics and pragmatic values in four varieties of English, as represented in the GloWbE corpus. These are, on the one hand, the two most influential inner circle varieties of English, those spoken in the United States and Great Britain, and, on the other, two outer circle varieties spoken in former colonies of these two countries, namely the Philippines and Singapore respectively. The results strengthen the understanding of the effects of global processes such as Americanization and glocalization on pragmatic variation and illustrate phenomena of linguistic convergence and divergence across space.Aquest llibre contribueix al camp de la variació pragmàtica en les llengües angleses del món analitzant els marcadors pragmàtics “kind of” i “sort of”. Després d’una revisió general de la seua història i ús actual, el llibre n’ofereix un estudi contrastiu de la freqüència, semàntica i valors pragmàtics en quatre varietats d’anglès, representades en el corpus GloWbE. Es tracta, d’una banda, de les dues varietats més influents de l’anglès del cercle intern, les parlades als Estats Units i Gran Bretanya, i, per un altre, de dues varietats del cercle extern parlades en antigues colònies d’aquests dos països, Filipines i Singapur, respectivament. Els resultats reforcen la comprensió dels efectes de processos globals com l’americanització i la glocalització en la variació pragmàtica i il·lustren fenòmens de convergència i divergència lingüística a través de l’espai.
Keywords: Pragmatics; World Englishes; Variationist Linguistics; Americanization; Dialect convergence; Dilaect divergence; Globalization